The Effect of Live Streaming Sales and Store Atmosphere Digital on Generation Z Impulsive Buying Decisions in TikTok Shop (A Case Study in Kelurahan Abianbase) - I Gusti Ngurah Bayu Segara; I Gusti Ngurah Sanjaya; Wayan Gede Suka Parwita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to determine the partial and simultaneous effects of live streaming sales and store atmosphere digital on impulsive buying decisions among Generation Z at TikTok Shop. Conducted in Kelurahan Abianbase, this quantitative research utilized a purposive sampling method, gathering primary data from 130 respondents through structured questionnaires. The data were analyzed using multiple linear regression. The results demonstrated that live streaming sales exerted a positive and significant effect on impulsive buying. Similarly, store atmosphere digital had a positive and significant impact. Simultaneously, both variables significantly enhanced impulsive buying decisions. Strategic recommendations include standardizing real-time information delivery during live sessions and establishing a uniform visual design for digital stores.